The overview of knowledge management for the benefits of service-based value in the university libraries:: A systematic literature review - Mostofa, Sk Mamun (Papanda Publisher, 2024)
There is an exclusive chance for university libraries to contribute to the future reimagining of library services. In this regard, the job of KM might be extremely successful. As a result, university libraries may provide excellent user services by utilizing KM. This research is to explore the existing models of Knowledge Management (KM) and how the existing models of KM are implemented at university libraries, to recognize how KM is being implemented at university libraries as reported in earlier research, and the benefits of KM practices for creating service value for libraries. This research was performed following the “Preferred reporting items for systematic reviews and meta-analyses (PRISMA)” guidelines. The study found that a skilled workforce and expertise are required for effective KM implementation in university libraries. Outdated skills may serve as a starting point for KM in university libraries, but they are insufficient for providing service-based value. There is a need for Library and Information Science (LIS) professionals to develop additional competencies for KM practice in university libraries. Based on the findings and discussion, it can be concluded that all the authors have recognized the importance of KM in libraries. This finding would aid the university libraries and offer current KM knowledge to other libraries. Therefore, this research would be an excellent addition to the application of KM in university libraries.